2014
DOI: 10.1371/journal.pone.0099606
|View full text |Cite
|
Sign up to set email alerts
|

Audio-Tactile Integration in Congenitally and Late Deaf Cochlear Implant Users

Abstract: Several studies conducted in mammals and humans have shown that multisensory processing may be impaired following congenital sensory loss and in particular if no experience is achieved within specific early developmental time windows known as sensitive periods. In this study we investigated whether basic multisensory abilities are impaired in hearing-restored individuals with deafness acquired at different stages of development. To this aim, we tested congenitally and late deaf cochlear implant (CI) recipients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 34 publications
(57 reference statements)
5
18
0
Order By: Relevance
“…The redundant signals effect (i.e., significantly faster RTs to the audio–visual compared with the fastest modality‐specific condition) was recognized in each group. This effect has been previously reported in NH listeners [e.g., Girard et al, ; Mahoney et al, ] and in CI patients [e.g., Nava et al, ; Schierholz et al, ]. Hence, our results extend previous findings by showing that a redundant signals effect also exists in patients with central auditory prostheses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The redundant signals effect (i.e., significantly faster RTs to the audio–visual compared with the fastest modality‐specific condition) was recognized in each group. This effect has been previously reported in NH listeners [e.g., Girard et al, ; Mahoney et al, ] and in CI patients [e.g., Nava et al, ; Schierholz et al, ]. Hence, our results extend previous findings by showing that a redundant signals effect also exists in patients with central auditory prostheses.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding CI patients, the Gain RT was not as strong. This is in line with findings of earlier studies, reporting no difference in multisensory Gain RT between post-lingually deafened CI patients and NH listeners [Nava et al, 2014;Schierholz et al, 2015]. The discrepancy between the groups of patients might be caused by the differential use of compensation strategies.…”
Section: Performance In the Speeded Response Tasksupporting
confidence: 92%
“…All four groups showed a remarkable audioevisual gain, which was comparable between the two hearing groups (NH, CI) and the two age groups (young, elderly). This replicates the finding from a previous study which reported comparable multisensory gain for audio-tactile processing in late-deafened CI users and NH listeners (Nava et al, 2014). Interestingly, the same study observed a lower multisensory gain specifically in early deafened CI users (Nava et al, 2014).…”
Section: Multisensory Integration In CI Userssupporting
confidence: 91%
“…This replicates the finding from a previous study which reported comparable multisensory gain for audio-tactile processing in late-deafened CI users and NH listeners (Nava et al, 2014). Interestingly, the same study observed a lower multisensory gain specifically in early deafened CI users (Nava et al, 2014). Together with the results of early deafened CI children, the findings of early deafened (late implanted) adult CI users suggest that hearing loss at young age can lead to decreased multisensory interactions and stronger dominance of vision (Gilley et al, 2010;Schorr et al, 2005).…”
Section: Multisensory Integration In CI Userssupporting
confidence: 89%
“…Investigations aimed to understand whether this plasticity is dependent on the extent of hearing loss revealed that while the auditory association areas are activated in subjects with total or partial hearing loss, AI was activated only in the subjects with total hearing loss (Lambertz, et al, 2005). Interestingly, studies in subjects with temporary auditory deprivation that was restored by cochlear implants showed that temporary deafness can impair multisensory (audio-tactile) integration (Landry, et al, 2013, Nava, et al, 2014). More specifically, the subjects were tested using the audiotactile illusory-flash effect (Hotting and Roder, 2004) in which simultaneous presentation of a somatosensory stimulus with a large number of successive non-speech sounds can lead to as many tactile as auditory perceptions in normal hearing individuals.…”
Section: Multisensory Integration In the Auditory Cortexmentioning
confidence: 99%